Fundamentals of Materials Science c y Eric J. Mittemeijer. - Mittemeijer, Eric J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book offers a strong introduction to fundamental concepts on the basis of materials science. It conveys the central issue of materials science, distinguishing it from merely solid state physics and solid state chemistry, namely to develop models that provide the relation between the microstructure and the properties. The book is meant to be used in the beginning of a materials science and engineering study as well as throughout an entire undergraduate and even graduate study as a solid background against which specialized texts can be studied. Topics dealt with are "crystallography", "lattice defects", "microstructural analysis", "phase equilibria and transformations" and "mechanical strength". After the basic chapters the coverage of topics occurs to an extent surpassing what can be offered in a freshman's course. About the author Prof. Mittemeijer is one of the top scientists in materials science, whose perceptiveness and insight have led to important achievements. This book witnesses of his knowledge and panoramic overview and profound understanding of the field. He is a director of the Max Planck Institute for Metals Research in Stuttgart.
Introduction -- electronic structure of the atom -- chemical bonding in solids -- crystallography -- the crystal imperfection; lattice defects -- analysis of the microstructure; analysis of lattice imperfections -- phase equilibria -- diffusion -- phase transformations -- recovery, recrystallization and grain growth -- mechanical strength of materials.
Keywords: Chemistry, Physical organic; Materials; Surfaces (Physics).; Materials Science; Metallic Materials; Continuum Mechanics and Mechanics of Materials; Condensed Matter Physics; Physical Chemistry; Structural Materials; Characterization and Evaluation of Materials